1992
DOI: 10.1080/03014469200002322
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships of the populations in eastern India

Abstract: The genetic relationships for four sets of populations in eastern India have been studied by using gene frequency data available in the literature. The Caucasoid populations in Assam and West Bengal are genetically close but different from the Mongoloid populations in the neighbourhood. The genetic distance analysis shows that the Mongoloid populations in Assam and West Bengal cluster according to their states of residence, indicating a correlation between genetic and geographical distances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…In this region, geographic contiguity is a better predictor of genetic similarity than culture. Both tribes are located in the hills surrounding the city of Shillong, and the Karbi and Khasi appear to be close kin, based on genetic analysis of six polymorphic loci (17). The villagers in both societies are agriculturalist and subsist primarily off rice, with little variation in wealth or diet.…”
Section: Resultsmentioning
confidence: 99%
“…In this region, geographic contiguity is a better predictor of genetic similarity than culture. Both tribes are located in the hills surrounding the city of Shillong, and the Karbi and Khasi appear to be close kin, based on genetic analysis of six polymorphic loci (17). The villagers in both societies are agriculturalist and subsist primarily off rice, with little variation in wealth or diet.…”
Section: Resultsmentioning
confidence: 99%
“…Another reason to carry out this genetic study on the Bihar population is because there has been coexistence and close interaction of higher and lower caste strata since bonded labour was practised in the state, and the entire family of the lower community was dependent on the employer's mercy and was at their disposal, probably resulting in gene flow. Studies based upon serological markers (Pandey et al 2000) and other protein markers (Roychoudhury 1981, 1992, Chakraborty et al 1986, Saha et al 1992 have been reported on a few tribal groups of the state to understand the diversity and gene flow among them. Since microsatellite markers are more informative than classical serological and other protein markers, in the current study, 15 microsatellite markers present in the Combined DNA Index System (CODIS), validated for the population of India, were chosen to estimate the impact of the deep-seated man-made caste system on the gene flow among four socio-culturally predominant caste groups (Brahmin, Bhumihar, Rajput and Kayasth) of Bihar.…”
Section: Introductionmentioning
confidence: 97%
“…Ethnically, the Bengalee population is a heterogeneous group comprising of Caucasoid, Proto-australoid and Mongoloid strains [15,16]. The populations living in the northern parts of the state of West Bengal show Mongoloid affiliation, whereas those in the southern regions show affinities especially with the Proto-Australoid and Caucasoid elements [17].…”
Section: Methodsmentioning
confidence: 99%